Re: Sancar S, Demirci H, Guzelsoy M, et. al. Fear of Circumcision in Boys Considerably Vanishes within Ten Days of Procedure. Urol J. 2016 Mar 5-2541:)1(13;5. - Sertkaya, Zülfü (Urology Journal, 2016)